MENILAI KEEFEKTIFAN PROGRAM PEMBERDAYAAN KELOMPOK WANITA NELAYAN DALAM PENINGKATAN KEMAMPUAN DAN PEREKONOMIAN MASYARAKAT: STUDI KASUS PROGRAM HOLISTIK PEMBINAAN DAN PEMBERDAYAAN DESA (PHP2D) DI KELOMPOK NELAYAN KAMPUNG BAJO KELURAHAN ANAIWOI, KABUPATEN KOLAKA, SULAWESI TENGGARA - Prihantini, Campina Illa; Soleha, Dini; Syahrir (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2023)
This research aims to analyze the impact felt by the community after participating in community service activities for the Village Community Service and Empowerment Grant Program (PHP2D). The analysis used is an analysis of the perceptions of the program recipients regarding their level of understanding, level of ability or skill, and level of income after the program ends. Respondents are the community recipients of the program so the method for determining respondents is the Purposive Sampling Method, totaling 30 people. The results of perception analysis using a Likert scale show that the level of understanding of the community has understood what has been conveyed in the program activities, with a percentage value of 60% of respondents understanding, the level of ability or skill of the community has changed greatly, with a percentage of 70% of respondents really understanding, while for the level of income The community is still in the fixed category, where the percentage value of 86.66% of respondents stated that there had been no change in income from the program.